Rare presentation of scar endometriosis in atypical and typical locations: a case series - Sinha, Maruti; Rani, Rekha; Gupta, Kavita; Sharma, Hitesha (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2026)
Scar endometriosis is an uncommon but well-documented entity resulting from the iatrogenic implantation of endometrial tissue into surgical scars. It is most frequently seen following caesarean section or other obstetric and gynaecological procedures and is often misdiagnosed due to its rarity and variable presentation. This case series presents patients with scar endometriosis involving both classical and unusual sites, highlighting diagnostic challenges and management outcomes. Patients with clinically and histopathologically confirmed scar endometriosis managed at Kasturba Hospital, Delhi over a two-year period were evaluated with respect to presenting symptoms, site of involvement, surgical history, diagnostic work-up, treatment, and follow-up. All patients presented with cyclical pain and swelling at or near surgical scars, with some demonstrating uncommon locations such as the episiotomy scar, umbilicus, and lateral abdominal wall. Surgical excision of the lesions with clear margins resulted in complete symptom relief in all cases. Histopathological examination confirmed the presence of endometrial glands and stroma in all excised specimens. No recurrence was observed during the follow-up period. Scar endometriosis should be suspected in women presenting with cyclical pain and swelling at or near surgical scars, particularly following obstetric or gynaecological procedures. Awareness of atypical presentations facilitates early diagnosis and effective surgical management.